2016
DOI: 10.1523/eneuro.0045-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contributions of Olfactory Receptor Neurons in a Drosophila Olfactory Circuit

Abstract: The ability of an animal to detect, discriminate, and respond to odors depends on the functions of its olfactory receptor neurons (ORNs). The extent to which each ORN, upon activation, contributes to chemotaxis is not well understood. We hypothesized that strong activation of each ORN elicits a different behavioral response in the Drosophila melanogaster larva by differentially affecting the composition of its navigational behavior. To test this hypothesis, we exposed Drosophila larvae to specific odorants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…To demonstrate the specificity of ORN activation, our method was successfully applied to determine the impact of two different ORN (ORN::7a & ORN::42a) (ORNs expressing either Or7a or Or42a) activation on larval behavior (Figure 3). Consistent with recent studies that individual larval ORNs are functionally distinct 1,10,13 , our representative data demonstrates that when ORN::7a expressing CsChrimson was stimulated by light, there was a significant decrease in run length compared to control animals. Conversely, when ORN::42a expressing CsChrimson was stimulated by light, there was a significant increase in run length compared to control animals (Figure 3).…”
Section: Representative Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To demonstrate the specificity of ORN activation, our method was successfully applied to determine the impact of two different ORN (ORN::7a & ORN::42a) (ORNs expressing either Or7a or Or42a) activation on larval behavior (Figure 3). Consistent with recent studies that individual larval ORNs are functionally distinct 1,10,13 , our representative data demonstrates that when ORN::7a expressing CsChrimson was stimulated by light, there was a significant decrease in run length compared to control animals. Conversely, when ORN::42a expressing CsChrimson was stimulated by light, there was a significant increase in run length compared to control animals (Figure 3).…”
Section: Representative Resultssupporting
confidence: 91%
“…The error bars represent SEM. While we describe only a single behavior parameter (run length) here, we note that each larval track can be further analyzed to calculate parameters for speed, path curvature, and body bends 1,8,13,14,15 . More parameters related to directionality such as heading angle, run length and run speed toward and away from odors can be obtained if an odor source is provided on one side of the arena 1,8,13 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…This study along with previous studies from our lab and others raise the possibility that starvation differentially modulates individual OSNs. Indeed, individual OSNs exhibit functional diversity that may lend them to differential modulation by the animal's internal state [46][47][48] . This diversity may stem from heterogeneous GABA B R levels on the terminals of individual OSNs that determine differential presynaptic gain control 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of memory by artificial activation of ORNs is not limited to ORN 47a given that an EA memory can be formed through the activation of ORNS 42b ( Figure 10 ). However, for each of the 21 ORNs, odor-specific associative processes have to be tested, as several studies have shown the presence of non-equivalency among larval ORNs ( Mathew et al, 2013 ; Hernandez-Nunez et al, 2015 ; Newquist et al, 2016 ). ORN 42a, for instance, unlike many other larval ORNs was shown to respond to a wide range of odors ( Kreher et al, 2005 ; Hoare et al, 2011 ; Mathew et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%